Influence of Coagulation on the Activation of Plasminogen by Streptokinase and Urokinase - Takada, Akikazu; Urano, Tetsumei; Takada, Yumiko (Thrombosis and Haemostasis, 1979)
Human plasma was mixed with Ca++ or thrombin, and urokinase (UK) or streptokinase (SK) and a chromogenic substrate (S-2251: H-D-Val-Leu-Lys-pNA) specific to plasmin. The hydrolysis of S-2251 was higher when clot was formed by the addition of Ca++ or thrombin than in the absence of clot. The hydrolysis of S-2251 by euglobulin in the presence of UK was also higher when clot was formed, thus, inhibitors may not be related to the better activation of plasminogen, in the presence of fibrin clot. It may be suggested that plasminogen was better activated by activators (UK and SK) in the clot than in its absence.